Die voorstelling van VIGS-verwante stigma in ’n versameling gedigte deur Afrikaanssprekende hoërskoolleerders - Carstens, A. (Koers, 2004)
The representation of AIDS-related stigma in a collection of poems by Afrikaans-speaking teenagers This article reports on a discourse analysis of twenty-two poems written by a group of white South African teenagers, with special reference to the construal of people living with HIV/AIDS and the role that stigmatisation plays. The vantage point is that of Christian ethics, while psycho-social models of stigma, and the archetypes of people living with HIV/AIDS (as portrayed by the media) serve as the descriptive framework. The most salient stigma-enhancing factor was found to be the perception that self-stigmatisation is an undeniable reaction to the disease. Although coming to terms with one’s HIV status by finding a deeper meaning in the disease can be regarded as a stigma-reducing response, it may be harmful if personal responsibility for one’s physical and mental well-being is not acknowledged and exercised. The article concludes with a number of recommendations regarding destigmatising intervention messages based on ethical principles.